Assessment of the Effects of Chemotherapy on Ovarian Reserve in Rats - Ahmet Mete Ergenoğlu; Özgür Yeniel; Volkan Turan; Gülşah Demirtaş; Levent Akman; Mustafa Coşan Terek; Gülinnaz Ercan; Osman Zekioğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To determine the effect of cyclophosphamide and cisplatin on ovarian reserve in rats by the way of counting primordial follicle and assessing TNF-alpha, 8-OH deguanosine and oxidant/antioxidant status. STUDY DESIGN: Thirty Wistar rats were divided into three groups. Cisplatin was administered at a dose of 5 mg/kg (Cisplatin group, n=10), cyclophosphamide was administered at a dose of 6 mg/kg (Cyclophosphamide group, n=10) and control group was only given sterile saline (Control group, n=10) in Ege University Faculty of Medicine. All injections were administered intraperitoneally at a single dose. At the end of the 7th day blood samples were drawn by intracardiac aspiration and bilateral extirpation of ovaries were performed. The number of primordial follicles, levels of TNF-alpha, 8-OH deoxyguanosine, malondialdehyde (MDA) and catalase enzyme activities were evaluated. RESULTS: The number of primordial follicles in the control group, cisplatin group and cyclophosphamide group were 27.5±4.7;17.3±2.1;17±1.4, respectively (p=0.156). While the levels of TNF-alpha were significantly higher in cisplatin group (p<0,001), 8-OH deoxyguanosine levels did not have significant difference among three groups (p=0.431). The levels of MDA were significantly lower compared to the other groups (p<0.001); however, the catalase enzyme activities did not show statistically significant difference. CONCLUSIONS: Insignificant depletion of primordial follicles was observed by using specified doses of chemotherapeutics. An increase in TNF-alpha and MDA levels may play a role in the development of ovarian tissue damage.